2016
DOI: 10.1016/j.rse.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Leaf spectral clusters as potential optical leaf functional types within California ecosystems

Abstract: a b s t r a c tOur ability to measure and map plant function at multiple ecological scales is critical for understanding current and future changes in Earth's ecosystems and the global carbon budget. Conventional plant functional types (cPFTs) based on a few productivity-related traits have been previously used to simplify and represent major differences in global plant functions, but more recent research has directly focused on the use of functional trait information. Still, sampling limitations have constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 100 publications
0
8
1
Order By: Relevance
“…Drawing general conclusions about interspecies differences and their magnitude compared to other factors is however difficult, because most studies (Table 1, Appendix A) are local, with only few species and sites measured, and data across campaigns cannot be readily compared, due to methodological differences. Studies that have examined a large number of species, using comparable methodology for each, clearly show that species is important, although not the only factor explaining spectral differences [11,30,33]. For example, for a set of 12 boreal species belonging to five taxonomic genera, species explained up to 71%, 70%, and 78% of variability in the reflectance, transmittance, and albedo spectra, respectively [11].…”
Section: Interspecific Variation In Needle Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing general conclusions about interspecies differences and their magnitude compared to other factors is however difficult, because most studies (Table 1, Appendix A) are local, with only few species and sites measured, and data across campaigns cannot be readily compared, due to methodological differences. Studies that have examined a large number of species, using comparable methodology for each, clearly show that species is important, although not the only factor explaining spectral differences [11,30,33]. For example, for a set of 12 boreal species belonging to five taxonomic genera, species explained up to 71%, 70%, and 78% of variability in the reflectance, transmittance, and albedo spectra, respectively [11].…”
Section: Interspecific Variation In Needle Spectramentioning
confidence: 99%
“…For example, for a set of 12 boreal species belonging to five taxonomic genera, species explained up to 71%, 70%, and 78% of variability in the reflectance, transmittance, and albedo spectra, respectively [11]. On the other hand, a study containing 18 plant species (of which 7 were conifers) in California, USA, reported that species explained 20%, 80%, and 47% of variability in the three first principal components derived from the reflectance spectra [33]. In addition, for four temperate and boreal species in North America, it was shown that differences (range) in photochemical reflectance index (PRI) were larger between species than between light conditions [30].…”
Section: Interspecific Variation In Needle Spectramentioning
confidence: 99%
“…For example, if maps of foliar nitrogen concentration and LMA were available, one might find that one of those traits is very random at a certain scale, while the other is very patchy, suggesting something about the environmental vs. biological controls on those two traits at that scale. Since PCs maximize variation and are non‐spatial, we can assume that the first few PCs from hyperspectral data likely correlate with the most variable top‐of‐canopy structural and chemical traits (Roth et al ), but I have not demonstrated that here.…”
Section: Discussionmentioning
confidence: 90%
“…Next, we employed a hierarchical clustering analysis to study the grouping of the samples based on their spectral information (e.g. Rees et al, 2004 ; Roth et al, 2016 ). The algorithm starts by assigning each observation to its own cluster and continues with merging the clusters closest in the distance space, finally forming a cluster tree.…”
Section: Methodsmentioning
confidence: 99%